Tribalism in Basrah after 2003: A Political Philosophical Approach to Understanding - Nasir Rahai, Prof. Dr. Qais (Basra studies journal, 2025)
The phenomenon of tribalism can be examined through multiple theoretical frameworks. This study adopts political philosophy as a lens to explore tribalism, focusing on the city of Basrah in the period following 2003. This year represents a pivotal moment in Iraq's history, marking the collapse of a repressive regime and the beginning of a transition toward democratic governance. Within this context, political philosophy provides critical tools for analyzing tribalism as a traditional social structure embedded in various societies. The study draws a clear distinction between the concept of the tribe as a lineage-based social unit and tribalism as a behavioral pattern shaped by authority and customary practices. These patterns significantly influence the formation of political identity, often manifesting in electoral processes, whether democratic or otherwise. This dynamic is particularly evident in Basrah’s post-2003 sociopolitical landscape, where the social function of tribalism and its various representations are analyzed.